Endoscopic Management of Chronic Subdural Hematoma - Yadav, Yad Ram; Ratre, Shailendra; Parihar, Vijay; Bajaj, Jitin; Sinha, Mallika; Kumar, Ambuj (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background Twist drill evacuation, burr hole aspiration, mini-craniotomy, and craniotomy are some of the surgical methods to remove chronic subdural hematoma (CSDH). Endoscopic treatment was also recently found to be useful.Methods We conducted a prospective study of 72 hematomas in 68 patients. Computed tomography was performed in all cases. Endoscopic surgery was performed in all CSDH patients.Surgical procedure A 4-cm skin incision was performed at the most curved part of skull with the CSDH. A mini-craniotomy or enlarged burr hole was made. The inner and outer table of the burr hole margin was drilled to provide a straight trajectory to the hematoma cavity. An endoscope supported by a telescope holder was used. A modified silicone brain retractor was used in five patients. A subgaleal drain was left in all patients for 3 to 5 days.Results There were 42 male and 26 female patients. The age ranged from 45 to 79 years (average: 69 years). All patients had a history of head trauma. Preoperative average Glasgow Coma Scale Score was 14. The procedure was effective in hematoma evacuation and a good visualization of the whole cavity in all patients. The endoscopic technique helped in complete hematoma removal in organized/solid clot, septations, and bridging vessels in 17, 2, and 2 cases, respectively. Duration of surgery ranged from 35 to 80 minutes. One death occurred. There was no recurrence, infection, fresh bleed, or injury to the brain or membrane.Conclusion The endoscopic technique is an effective alternative technique for treating CSDH. Although the study has limitations because of the small number of patients with a short follow-up, the study indicated that thick and vascular membranes, septations, and organized and solid clots can be removed effectively using this technique.
Keywords: chronic subdural hematoma; endoscopic surgical procedure; minimally invasive neurosurgery; neuroendoscopy; traumatic intracranial subdural hematoma.